Conceptualising ‘diaspora diplomacy’: Territory and populations betwixt the domestic and foreign - Ho, E; Mcconnell, F (SAGE Publications, 2017)
This article bridges diaspora studies and diplomacy studies by proposing the concept of ‘diaspora diplomacy’, which considers the components of diplomacy and the changing relationships that diasporas have with states and other diplomatic actors. First, we ask who are the key actors engaged in diaspora diplomacy? Second, how is diplomatic work enacted by and through diasporas? Third, what are the geographies of diaspora diplomacy? Diaspora diplomacy directs researchers to reconsider the distinction between domestic and foreign policy, and the territorial dimensions of both diaspora and diplomacy. We engage with assemblage theory, highlighting the polylateral and multi-directional aspects of diaspora diplomacy.